Legal Analysis of Illegal Animal Trade In Surabaya - Muhammad Faishal Mahdy; M. Hidayat; Priambodo Adi Wibowo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
The aim of the research is to determine the legal protection for criminal acts in the trade in protected animals in Surabaya. The research method is normative juridical research, namely research that describes in detail the social phenomena that are the main problems in everyday life in relation to the applicable positive criminal law regulations. The results of criminal law enforcement regarding the protection of protected wild animals, especially those that occurred in the Surabaya District Court area with Case Register Number 2451/Pid.B/LH/2023/PN Sby, show efforts to enforce criminal law, namely declaring defendant I MUHAMMAD SOFYAN UMAR, defendant II INDRI SETIAWAN, and defendant II BENI KRISTIANTO have been legally and convincingly proven guilty of committing the criminal act of participating in intentionally keeping and trading in protected animals while alive, guilty and possibly guilty of committing the criminal act of